Immune checkpoint inhibitor-associated acute kidney injury and mortality: An observational study. - Marije S Koks; Gurbey Ocak; Britt B M Suelmann; Cornelia A R Hulsbergen-Veelken; Saskia Haitjema; Marieke E Vianen; Marianne C Verhaar; Karin A H Kaasjager; Meriem Khairoun (PLoS ONE)
Background Immune checkpoint inhibitors, approved for the treatment of various types of cancer, are known to cause a unique spectrum of side effects, including acute kidney injury (AKI). The aim of this study was to describe the incidence, risk factors, renal outcomes, and mortality of AKI in patients receiving checkpoint inhibitors. Methods Patients receiving checkpoint inhibitors between January 2013 and May 2020 at the University Medical Center Utrecht, the Netherlands, were identified using the Utrecht Patient Oriented Database. AKI was defined as an increase in serum creatinine of ≥1.5 times the baseline value, based on the Kidney Disease: Improving Global Outcomes criteria. Cox proportional hazard regression analysis was used to assess risk factors for AKI and to evaluate the relationship between AKI and mortality. Persistent renal dysfunction was diagnosed in AKI patients with a final serum creatinine measurement of >1.3 times the baseline value. Results Among 676 patients receiving checkpoint inhibitors, the overall incidence of AKI was 14.2%. Baseline variables independently associated with AKI were a gynecologic malignancy, monotherapy with ipilimumab, and the use of a diuretic, angiotensin-converting enzyme inhibitor or angiotensin-receptor blocker, or proton pump inhibitor at baseline. AKI was checkpoint inhibitor-associated in one third of all patients with AKI. Checkpoint inhibitor-associated AKI was mostly low-grade, occurred a median of 15 weeks after checkpoint inhibitor initiation, and resulted in persistent renal dysfunction in approximately 40% of the patients. Patients with all-cause AKI had a twofold increased mortality risk, but checkpoint inhibitor-associated AKI was not associated with increased mortality. Conclusions In this study, patients receiving checkpoint inhibitors frequently developed AKI due to various etiologies. AKI directly related to the effect of checkpoint inhibitor toxicity did not increase mortality. However, AKI not related to the effect of checkpoint inhibitor toxicity was associated with increased mortality.